Pengembangan Aplikasi Mobile untuk Meningkatkan Kesehatan Mental di Kalangan Remaja - semin, semin (MUJAHADA: Jurnal Pengabdian Masyarakat, 2023)
This research focuses on the development of a mobile application aimed at improving mental health among adolescents. The study recognizes the importance of addressing mental health issues in the adolescent population and the potential of mobile technology in providing accessible and effective interventions. The mobile application incorporates features such as mood tracking, relaxation exercises, mental health information, and access to support resources. Through a community engagement approach, the application was developed and evaluated in collaboration with adolescents. The results indicate that the mobile application provided valuable support for adolescents in managing their mental health and resulted in positive changes in their well-being. The findings highlight the significance of integrating technology-based interventions into existing mental health services for a holistic approach in promoting adolescent mental health.